DEVELOPING THE NATIONAL QUALIFICATIONS FRAMEWORK: KYRGYZ EXPERIENCE OF QUALIFICATIONS ANALYSIS IN THE AGRICULTURAL SECTOR - Мasuma I. Bashirova; Farida I. Ryskulueva (Russian State Vocational Pedagogical University, 2015)
The paper reveals the research outcomes concerning the qualifications requirements of the Kyrgyz Republic's agricultural sector; the significance of the given sector and lack of competent specialists determine the research relevance. The methodology bases of quantitative and qualitative human resources analysis involved a traditional sociological survey and innovative methods of functional analysis. The research findings can be used for balancing the labor marker supply and demand, and ensure, therefore, the effective personnel management in agricultural industry. On the other hand, the above findings can improve the vocational training programs and mechanisms of training quality assessment to align them with the employers' requirements.